2016
DOI: 10.1002/ece3.2377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of flower scent inSileneaereveal a contrasting phylogenetic signal between night and day emissions

Abstract: Flower scents are complex blends of volatile compounds often shaped by selection pressures exerted by mutualistic and antagonistic interaction partners, but also by phylogenetic constraints. So far, little is known about the relative effect of selection and phylogenetic signal on scent patterns, and no study to date analyzed the phylogenetic signal in multivariate semiquantitative scent patterns. We analyzed the phylogenetic signal in qualitative and semi-quantitative patterns of flower scents in 47 Sileneae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 89 publications
(160 reference statements)
4
14
0
Order By: Relevance
“…Perhaps due in part to the technical aspects of its quantification, the evolution floral scent has traditionally received less attention in a phylogenetic framework compared to other floral traits, such as floral color and shape (e.g., Gómez et al 2006;Harder and Johnson 2009). However, other studies that have investigated the evolution of scent profiles using phylogenies have generally found scent to be a complex and highly variable trait across closely related taxa (e.g., Azuma et al 1999;Prieto-Benítez et al 2016), consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
“…Perhaps due in part to the technical aspects of its quantification, the evolution floral scent has traditionally received less attention in a phylogenetic framework compared to other floral traits, such as floral color and shape (e.g., Gómez et al 2006;Harder and Johnson 2009). However, other studies that have investigated the evolution of scent profiles using phylogenies have generally found scent to be a complex and highly variable trait across closely related taxa (e.g., Azuma et al 1999;Prieto-Benítez et al 2016), consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
“…Because several nodes of our tree were not supported, our results may be affected by phylogenetic uncertainty; however, the pPCA showed that the phylogenetic signal was mainly carried by compounds produced by the yellow‐flowered species O. corsica , O. lutea and O. sicula , which were found to be closely related, with moderate to strong support. Such a phylogenetic signal in olfactory cues involved in pollinator attraction has been found in other studies, both in generalized (Prieto‐Benítez et al 2016) and specialized (Steiner et al 2011) pollination systems, and could result from phylogenetic constraints in the evolution of some biosynthetic pathways (Delle‐Vedove et al 2017). In contrast, in the genus Chiloglottis , no correlation between phylogenetic and chemical distances could be found (Peakall et al 2010), and speciation in this genus was even shown to be associated with shifts in floral scents.…”
Section: Discussionsupporting
confidence: 67%
“…Some authors have evaluated their usefulness for taxonomic or phylogenetic studies and concluded that floral odour was evolutionary labile, carrying little information on the phylogenetic history of the studied plant species (Williams & Whitten 1999; Levin et al 2003). However, the phylogenetic signal carried by floral scents was found to be significant in other cases (Steiner et al 2011; Schäffler et al 2012; Prieto‐Benítez et al 2016), although its strength was shown to vary among compound classes and pollination systems (Jürgens 2004; Schäffler et al 2012; Prieto‐Benítez et al 2016). In particular, this signal may be weak relative to the strength of pollinator‐mediated selection in specialized pollination systems in which assortative mating is ensured by specific olfactory signals, such as those described in orchids (Peakall et al 2010; Hetherington‐Rauth & Ramírez 2016; but see Steiner et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Components Analysis (pPCA) (Jombart et al 2010) and Pagel's λ (see Prieto-Benítez et al, 2016). pPCA creates two principal components (PCs) that summarize the phylogenetic resemblance in the phylogeny (see previous section) owed to pollinators.…”
Section: Phylogenetic Signal In Pollinatorsmentioning
confidence: 99%
“…For this analysis, we used the measure of phylogenetic proximity underlying the test of Abouheif (1999) because of its abilities in detecting phylogenetic signal (Pavoine et al, 2008). As pPCA does not explicitly test for the presence of a phylogenetic signal, we used Pagel's λ to test for a phylogenetic signal in the PCs (see Freckleton et al, 2002;Prieto-Benítez et al, 2016 (Freckleton et al, 2002). All analyses were implemented in R (R Core Team, 2014);…”
Section: Phylogenetic Signal In Pollinatorsmentioning
confidence: 99%